Outcomes of sutureless total thyroidectomy in elderly. (September 2016) - Tolone, Salvatore; Bondanese, Mariachiara; Ruggiero, Roberto; Gili, Simona; Pirozzi, Raffaele; Parisi, Simona; Buonomo, Nunziomattia; Napolitano, Vincenzo; Docimo, Ludovico; Docimo, Giovanni
Abstract: Introduction: Thyroid disease is common in elderly population. The incidence of hypothyroidism and multinodular goiter increases with age. Surgery in elderly patients has been considered to be more hazardous than in a youthful population. Besides the traditional surgical hemostatic techniques, different hemostatic approaches, which further minimize the risk of bleeding and complications during thyroidectomy, have become available. Aim of this study was to review and compare the outcomes of total thyroidectomy (TT) in elderly performed with different energy system. Methods: A total of 255 patients were eligible for the study and enrolled. One hundred and five patients with age >70 years (median age 76, range 70–90) constituted the elderly group (EG), whereas the young group (YG) was composed by 150 patients (median age 36, range 18–69). Each group was further divided into three subgroups, on the basis of the device used (none, Ligasure Precise/Small Jaw or Harmonic Focus) for performing TT as follows: conventional thyroidectomy in EG (CTE) and YG (CTY), Ligasure thyroidectomy (LTE and LTY) and Harmonic thyroidectomy (THE and HTY). Intra-operative and post-operative data, as well as complications rate, were collected. Results: There was no significant difference between the elderly and the young patients treated with total thyroidectomy. Using of Harmonic Focus or Ligasure Precise/Small Jaw allowed a reduction of the duration of surgery (p < 0.05) than conventional approach; complication rate for hemorrhage, hypocalcemia and vocal cord paralysis was similar in all sub-groups. Conclusions: Total thyroidectomy in elderly patients is as safe as in the younger population. Moreover, using the Harmonic Focus and the Ligasure Precise/Small Jaw is a safe, effective, and time-saving alternative to the traditional suture ligation technique for thyroid surgery.